Exame do corpo de delito na perícia veterinária (ensaio) - Tremori, Tália Missen [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2014)
Situations of cruelty to animals occur frequently and the veterinarian is the Professional more competent to perform expertise in these cases. The Forensic Veterinary Medicine is growing, and its goal is to protect wild and domestic animals, based on the law and taking into account the human. The veterinary medical expertise has always involved scientific and technical knowledge in order to clarify the facts and interpret trace events before criminals or suspects. The examination of the corpus delicti is the main way to evaluate a crime scene, through analysis, resulting in reports that assist the development of judicial procedures.

Casos envolvendo crueldade com animais acontecem com frequência e o médico-veterinário é o profissional mais competente, para realizar as respectivas perícias. A Medicina Veterinária Legal está em constante crescimento e o seu objetivo é proteger os animais domésticos e selvagens, com base na legislação e levando em consideração o ser humano. A perícia sempre envolveu conhecimentos técnico-científicos destinados à esclarecer os vestígios e interpretar fatos perante acontecimentos criminosos ou suspeitos. O exame do corpo de delito é a principal forma para a avaliação de um local de crime, com o emprego de uma análise minuciosa que resulte em laudos destinados ao auxílio e à condução de um processo judicial.
The examination of the corpus delicti in veterinary expertise
Keywords: Forensic veterinary medicine; Legal expert; Animal; Medicina veterinária legal; Perito criminal; Animal